HOW TEMPERAMENT AND PERSONALITY IMPACT SUBJECTIVE EXECUTIVE FUNCTION IN OLDER ADULTS. (11th November 2018) - Bell, T; Stavrinos, D
Abstract: Age-related declines in executive function (EF), the cognitive control of mental processes for goal-directed behavior, is common. However, there is significant variability among older adults on EF, with many showing little to no difficulty. To prevent dysfunction, there is a need to explain individual differences that maintain or worsen EF over time. Prior literature highlights the importance of personal traits on task-based EF but the relation with subjective difficulties is less clear. The current project examined temperament and personality on EF across two studies in community-dwelling older adults (65+, total n=75). Both studies measured subjective EF (Behavioral Rating Inventory of Executive Function-Adult) but separately administered scales on personality (Big-5) and temperament (Adult Temperament Questionnaire). Overall, more neurotic and less conscientious temperaments related to greater EF difficulties. Regarding personality, individuals with higher negative affect but lower effortful control reported more subjective EF problems. Findings elucidate ways to predict subjective cognitive impairment.